Ethical decision making: A review of the empirical literature - Ford, Robert C.; Richardson, Woodrow D. (1994)
The authors review the empirical literature in order to assess which variables are postulated as influencing ethical beliefs and decision making. The variables are divided into those unique to the individual decision maker and those considered situational in nature. Variables related to an individual decision maker examined in this review are nationality, religion, sex, age, education, employment, and personality. Situation specific variables examined in this review are referent groups, rewards and sanctions, codes of conduct, type of ethical conflict, organization effects, industry, and business competitiveness. The review identifies the variables that have been empirically tested in an effort to uncover what is known and what we need to know about the variables that are hypothesized as determinants of ethical decision behavior.
Keywords: Ethical Decision; Empirical Literature; Decision Maker; Economic Growth; Decision Making; Literaturbericht